Polish phenological camera network, NatureVido: implementation, capabilities, preliminary results - Różańska, Monika Anna; Józefczyk, Damian; Chojnicki, Bogdan Heronim (Acta Geographica Lodziensia, 2025)
In a changing climate, phenological observations are a key tool in assessing climate change impact on vegetation. Phenocameras are increasingly being used worldwide as a new tool in phenological research. The Polish Naturevido pheno-camera network, established in 2020, uses them to monitor various ecosystems, enabling analysis of both the whole vegetation cover and individual plants. To demonstrate the network’s capabilities, regions of interest (ROIs) representing woody species and herbaceous species separately were designated for images from 2024. Average colour parameters within each ROI have been calculated. Based on the phenophase extraction, start of season (SOS) was determined to range from day of the year (DOY) 79 to 119 and from DOY 64 to 113, for woody and herbaceous plants, respectively. End of season (EOS) ranged from DOY 282 to 314 for woody plants, and from DOY 200 to 40 (of following year) for herbaceous plants. EOS was determined within a wider uncertainty range than SOS. The most pronounced season-length difference was between peatland and urban sites.